LIQUIDITY AND PROFITABILITY RATIO ANALYSIS TO ASSESS THE COMPANY’S FINANCIAL PERFORMANCE AT PT. BANK RAKYAT INDONESIA (PERSERO) TBK. - Tarmizi Abbas; Wahyuddin Albra; Machfud; Wardhiah; Khairil Anwar (PT. Radja Intercontinental Publishing, 2024)
A bank is a business entity that collects funds from the public, and distributes them to the public in the form of credit with the aim of improving the standard of living of many people. Lately it is increasingly popular with the term healthy bank or unhealthy bank. The health of a bank can be seen from the ability of a bank to carry out banking operations normally and be able to fulfill all obligations properly in accordance with applicable banking regulations. The company's financial performance is closely related to the measurement and appraisal of performance within a company. The purpose of the company's ratio analysis is to know the level of liquidity, know the level of solvency, know the level of profitability, and know the level of stability. The profitability ratio that will be used to assess Bank Rakyat Indonesia's financial performance is classified into several parts, including Net Profit Margin, Return On Assets, and Return On Equity.